2021
DOI: 10.1016/j.jpeds.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical and Epidemiologic Characteristics of Young Febrile Infants with and without Severe Acute Respiratory Syndrome Coronavirus-2 Infection

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 28 publications
4
30
1
Order By: Relevance
“…Overall illness among infants with SARS-CoV-2 infection in this study was mild to moderate, consistent with the severity of disease in this age group previously reported. 26,28 A minority of infants with SARS-CoV-2 required respiratory support or ICU admission, consistent with the reported literature, 8,9,12,13,19,[28][29][30]32 although this may be confounded by our observed higher prevalence of comorbidities among infants without SARS-CoV-2 compared to infants with SARS-CoV-2. The median hospital LOS for SARS-CoV-2 positive infants in this study was shorter than previously reported 10,30 and all infants with SARS-CoV-2 survived to discharge, consistent with good outcomes reported across other studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall illness among infants with SARS-CoV-2 infection in this study was mild to moderate, consistent with the severity of disease in this age group previously reported. 26,28 A minority of infants with SARS-CoV-2 required respiratory support or ICU admission, consistent with the reported literature, 8,9,12,13,19,[28][29][30]32 although this may be confounded by our observed higher prevalence of comorbidities among infants without SARS-CoV-2 compared to infants with SARS-CoV-2. The median hospital LOS for SARS-CoV-2 positive infants in this study was shorter than previously reported 10,30 and all infants with SARS-CoV-2 survived to discharge, consistent with good outcomes reported across other studies.…”
Section: Discussionsupporting
confidence: 89%
“…5, 9-14, 20, 26, 27, 29-32 The mean age of all infants with SARS-CoV-2 infection in our study was higher than that of SARS-CoV-2 negative infants, but in line with mean or median ages (16-39 days) reported in other studies of infants undergoing SBI evaluation. 9,12,26,28,30 While this could reflect longer exposure to the extrauterine environment and more opportunities for viral transmission, inclusion of asymptomatic newborns exposed to maternal infections may have decreased the average age of SARS-CoV-2 negative infants, which may explain why this age difference was not observed in the febrile subgroup. The lower age among infants without SARS-CoV-2 infection may confound the differences in hemoglobin observed between all infants with and without SARS-CoV-2, since hemoglobin may be elevated shortly after birth and no hemoglobin differences were observed between SARS-CoV-2 positive and negative infants in the older, febrile subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…
in which 20 of 30 patients tested positive of SARS-CoV-2. 6 Neonates and infants with COVID-19 in that cohort had mild symptoms. 6 In addition, the present analysis found that the proportion of concomitant SBIs among young infants with SARS-CoV-2 infection was similar to the proportion of bacterial coinfection with other respiratory viruses before the pandemic.A limitation of this study is that tests were infrequently performed for respiratory viruses other than SARS-CoV-2 during the pandemic because reagents were in critical shortage.
…”
mentioning
confidence: 82%
“…in which 20 of 30 patients tested positive of SARS-CoV-2. 6 Neonates and infants with COVID-19 in that cohort had mild symptoms. 6 In addition, the present analysis found that the proportion of concomitant SBIs among young infants with SARS-CoV-2 infection was similar to the proportion of bacterial coinfection with other respiratory viruses before the pandemic.…”
mentioning
confidence: 82%
“…The authors showed that SARS-CoV-2-infected newborns more commonly exhibited lethargy or feeding difficulties and had lower white blood cell, neutrophil, and lymphocyte counts compared with febrile newborns that tested negative for SARS-CoV-2. However, with the exception of two of 20 newborns requiring supplemental oxygen, COVID-19 disease was generally mild with no newborn requiring intubation or other medical intervention [ 38 ▪▪ ]. The report from Sweden similarly showed mild disease course: in the 21 infants who tested positive for SARS-CoV-2 neonatally, none had congenital pneumonia, and none had morbidities with a clear link to SARS-CoV-2 [ 16 ▪▪ ].…”
Section: Outcomes In Newborns Infected With Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%